2015
DOI: 10.1016/j.foodhyd.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

The emulsification properties of octenyl- and dodecenyl- succinylated inulins

Abstract: a b s t r a c tThe emulsification properties of a series of inulin samples modified using varying amounts of octenyland dodecenyl-succinic anhydride have been studied by determining the droplet size as a function of time, temperature and in the presence of electrolyte using laser diffraction. It was found that~2% modified inulin was required to stabilise 15% w/v medium chain triglyceride emulsions and that the minimum droplet size was achieved when the % hydrophobe content was >8 mol%. The dodecenyl derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 12 publications
(15 reference statements)
5
9
0
Order By: Relevance
“…The same research group studied the emulsification properties of OSA inulin derivatives and DDSA-inulin derivatives in the presence of electrolytes and during storage. It was also revealed that the ∼2 % DDSA inulin derivative exhibited a smaller droplet size and produced stronger medium-chain triglyceride emulsions than the OSA inulin derivatives and Inutec®SP1 ( Kokubun et al, 2015 ). The high emulsion stability of OSA and DDSA inulin derivatives has been achieved due to the significantly shorter inulin chain and formation of electrostatic repulsive forces owing to the presence of carboxylate ions in the head group.…”
Section: Chemistry and Synthesis Of Hmimentioning
confidence: 98%
See 3 more Smart Citations
“…The same research group studied the emulsification properties of OSA inulin derivatives and DDSA-inulin derivatives in the presence of electrolytes and during storage. It was also revealed that the ∼2 % DDSA inulin derivative exhibited a smaller droplet size and produced stronger medium-chain triglyceride emulsions than the OSA inulin derivatives and Inutec®SP1 ( Kokubun et al, 2015 ). The high emulsion stability of OSA and DDSA inulin derivatives has been achieved due to the significantly shorter inulin chain and formation of electrostatic repulsive forces owing to the presence of carboxylate ions in the head group.…”
Section: Chemistry and Synthesis Of Hmimentioning
confidence: 98%
“… DDSA-inulin had much better emulsification properties than OSA-inulin and Inutec®SP1. Kokubun et al (2015) (2018) Inulin, coded Inutec H 25 P, Tween 20. Successfully synthesized in deionized water under alkaline conditions using ASA.…”
Section: Chemistry and Synthesis Of Hmimentioning
confidence: 99%
See 2 more Smart Citations
“…It is evident for Inutec SP1 that droplet aggregation is prevented through steric repulsive forces arising from the interaction of the carbohydrate moieties (Nestor et al, 2005;). For the OSA-and DDSA -inulin samples, which have a significantly shorter inulin chain compared to Inutec, stabilisation will be achieved by electrostatic repulsive forces due to the presence of the carboxylate ions in the head-group (Kokubun, Ratcliffe & Williams (2015)). This is supported by the zeta potential measurements reported above which show that the droplets acquire a significant negative charge as the pH is increased.…”
Section: Emulsification Propertiesmentioning
confidence: 99%